2022
DOI: 10.48550/arxiv.2204.05143
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Re-weighting dark matter in disc galaxies: a new general relativistic observational test

Abstract: A recent analysis of data from the ESA Gaia mission demonstrated that the kinematics of stars in the Milky Way can be modelled without invoking the presence of dark matter whatsoever. Indeed, the higher-than-Keplerian velocities observed in outer stars can be ascribed to the properties of the general relativistic (GR) metric assumed to describe the Galaxy. Here we generalize the concept, and derive the most general exact GR model for a stationary axi-symmetric dynamically cold dust structure. We explicitly sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Let us now compare the accepted special relativistic description (SR), which accounts only for the kinematic Doppler shift, to the general relativistic description (GR), which instead includes the gravitational shift effect. The expressions for the redshift for the model that we are considering were calculated by Astesiano et al [23], and read:…”
Section: B Light Frequency Shift Measured From An Inertial Asymptotic...mentioning
confidence: 99%
“…Let us now compare the accepted special relativistic description (SR), which accounts only for the kinematic Doppler shift, to the general relativistic description (GR), which instead includes the gravitational shift effect. The expressions for the redshift for the model that we are considering were calculated by Astesiano et al [23], and read:…”
Section: B Light Frequency Shift Measured From An Inertial Asymptotic...mentioning
confidence: 99%
“…They found that the Milky Way's rotation curve was equally well fit by both. The model was generalized by Astesiano et al [4,5], who again found that a purely GR analysis, without dark matter, could account for the observations. In the studies of Astesiano and Ruggiero [6] (hereafter AR22) and [7], the specific role of the post-Newtonian gravitomagnetic effect was made clear in these 'GR without Dark Matter' models.…”
Section: Introductionmentioning
confidence: 98%